Optimal crop plan of cooperative farmers in Osun state, Nigeria: a linear programming approach - Sofoluwe , N.A; Tijani, A.A (Applied Studies in Agribusiness and Commerce, 2021)
Optimal level of production requires better use of existing resources at the lowest possible cost. Despite the inherent advantage of cooperatives to the agricultural sector, the question of how farmers under cooperative umbrella use farm resource for optimal outcome remains unanswered. This study investigates optimal crop mix for cooperative farmers in rural communities in Southwest Nigeria. Primary data were collected for the study through structured questionnaire. The data were fitted to Linear Programming Model. Three different cropping patterns are identified among the cooperative farmers. Based on the results from linear programming model, only maize, cassava and yam are admitted in the final plan and this combination is to be produced at 2.23 hectares. The gross margin value associated with the plan is ₦156, 235.781 (1$ = N365). Input resources such as land, labour, fertilizer, and chemicals are not fully utilized. The slack values for these inputs are 0.31, 651.20, 1929.6 and 140.76 respectively. The sensitivity analysis shows that seed/seedling is the only binding resource in the final plan with a shadow price which suggests that proper allocation of seed and seedlings would improve returns to cooperative farmers. There is need for appropriate farm management strategies to ensure optimal return for farmers. More education and training is suggested to boost cooperative farmers understanding of optimum strategy that is needed to improve production and earnings.JEL code: Q10, Q13